Entre avanços e rupturas: análise do alcance do Programa de aquisição de Alimentos (PAA) em 10 anos de atuação – 2009 a 2019 - Natália Thaynã Farias Cavalcanti; Marta Cristina Marjotta-Maistro; Gilberto Gonçalves Rodrigues (Confins)
The Food Acquisition Program (PAA), sanctioned by Law No. 10,696 of July 2, 2003, has shown significant results in terms of access to food for vulnerable populations and in helping to strengthen family farming. Despite the progress made, the PAA has also faced weaknesses in its implementation which have affected its effectiveness and reach in Brazil. This work aims to identify the reach of the PAA by Brazilian region, analysing the amount of resources, products purchased, number of municipalities and suppliers participating in the Program from 2009 to 2019. The analysis and findings were based on a literature review and secondary data from the National Supply Company (CONAB), the main executor of the PAA, available on the Federal Government Platform. The results showed that the PAA presents ruptures and discontinuities in its execution, starting in 2013, in the variables analysed, after changes in operationalization and inspections. In the period 2009-2019, the scope of the Program, in terms of resources invested, fell by 88.6%, resulting in a reduction in the acquisition of more than 263,000 tons of food. The participation of municipalities fell by 63.5% and 92.1% in the number of suppliers, bringing the Program to an end and showing the weakening of specific agricultural policies for family farming.